If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.8y + 8x = 6 Reorder the terms: 8x + 3.8y = 6 Solving 8x + 3.8y = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3.8y' to each side of the equation. 8x + 3.8y + -3.8y = 6 + -3.8y Combine like terms: 3.8y + -3.8y = 0.0 8x + 0.0 = 6 + -3.8y 8x = 6 + -3.8y Divide each side by '8'. x = 0.75 + -0.475y Simplifying x = 0.75 + -0.475y
| -8x=-4(x-4) | | 2(2x-4)-x-3=-14 | | log(8x+6)=1 | | 6(3n+2)=9(5n+9)+2 | | X+5+3x+5+y+2y+15=180 | | x^2+4x+161=0 | | -2a-9=6x+15 | | -3x-45=-11x+51 | | f(x)=-12x+48 | | .3x-2.3=.1 | | 2(4y-3)=-10 | | -7w+2(w+4)=3 | | 8+x=-21 | | -32+t+18= | | 5y+12=57 | | 12=x^2-4 | | 10x+y=7(x+y) | | -25+2v=-56v-42 | | 50c+5f+10cr+fr=0 | | r^2-r+2=7 | | X+5+3x+5=180 | | y+3=-.5(x+5) | | 7b=6b-9 | | -5(2t-2)+6t=5t-6 | | (-19)+x=-33 | | 40=2y+12 | | 0.04(y-7)+0.12y=0.20y-.6 | | 36x^3-15x=0 | | Ax+5=bs-c | | k-4-6=-16 | | 3y-1=x+5 | | 3x^6+6x^4-24x^5=0 |